Impact of catastrophizing on pain during orthodontic treatment - Costa,Eduardo Oliveira da (2020)
ABSTRACT Objective: This study proposed to investigate the influence of catastrophizing and others factors related to pain during orthodontic treatment. Methods: 27 patients with 0.022 x 0.028-in Straight-wire brackets were evaluated during alignment and leveling phase with nickel-titanium wires. Visual Analog Scales measured the intensity of orthodontic pain at six moments after a clinical appointment: 6 first hours; 1, 2, 3, 5, and 7 days. Multiple linear regression and stepwise approach assessed the influence of the following variables on pain: catastrophizing, sex, age, duration of treatment, clinical appointment time (morning or afternoon), and wire diameter. Results: The highest pain intensity was reported 24 hours after activation. These data were used to analyze factors associated with pain level. Age (r = 0.062, p= 0.7586), sex (p= 0.28), catastrophizing (r = -0.268, p= 0.1765), and orthodontic wire diameter (r = 0.0245, p= 0.2181) were not correlated with orthodontic pain in the univariate statistics. Catastrophizing was included in the multiple regression model because it was of great interest. Duration of orthodontic treatment (r = 0.6045, p= 0.0008) and the time when orthodontic appliance was activated (p= 0.0106) showed statistical significant associations with pain, and were also included in the multivariate regression, which showed that about 32% of orthodontic pain could be explained by the duration of treatment (R2= 0.32, p= 0.0475). Catastrophizing (R2= 0.0006, p= 0.8881) and clinical appointment time were not significantly associated with pain (R2= 0.037, p= 0.2710). Conclusions: Pain after activation of fixed orthodontic appliance is not associated with catastrophizing as well as age, sex, orthodontic wire diameter, and period of activation.